JAPAN – U.S. BALLISTIC MISSILE DEFENSE COOPERATION: THE IMPLEMENTATION OF “THE JOINT STATEMENT OF THE SECURITY CONSULTATIVE COMMITTEE (SCC)” IN COUNTERING NORTH KOREA’S BALLISTIC MISSILES PROGRAM (2015-2019) - Febry Hadiaty; Anak Agung Banyu Perwita (Universitas Jenderal Ahmad Yani, 2020)
Asia-Pacific (now also known as Indo-Pacific) region has a highly complex geopolitics and strategic environment with the fact that some political confrontation and conflicts still remain unsolved within the region. One of important issues in the region also includes North Korea’s ballistic missiles program. This program has become a rapid growing threat for both regional and global security. The lack of accountability on the program and erratic leadership of Kim Jong-Un have also projected threats for the United States and its allies, including Japan. The alliance between Washington and Tokyo has been able to become a remarkable resilient security partnership and has served as the cornerstone for the region’s stability. Both countries have conducted many defense cooperation in several areas, including for ballistic missiles defense cooperation. As one of the forms of the ballistic missiles defense cooperation between Japan and the U.S., the Security Consultative Committee (SCC) as the alliance’s primary defense forum produces joint statement which also highlights the ballistic missiles defense cooperation of Japan and the U.S. to counter North Korea’s ballistic missiles program. Therefore, this article analyzes the implementation of the joint statement of the SCC in deterring North Korea’s ballistic missiles program, particularly the joint statement in the period of 2015 to 2019. In analyzing that, this article uses qualitative method that relies on the primary and secondary resources found that Japan and the U.S. implemented their joint statement of the SCC by enhancing the capabilities of their ballistic missiles defense system.